Robôs móveis roteadores aplicados à construção de redes ad-hoc - Elerson Rubens da Silva Santos (2015)
Mobile Robotics can help humanity in many tasks, including assistrescue operations in disasters. In environments with no communicationinfrastructures, it is important to establish an ad-hoc network toallow rescue teams to communicate. This work investigates the problemof deploying a set of networked robots to create an ad-hoc networkinterconnecting a set of static clients, allowing the clients tocommunicate among themselves. The proposed approach has two phases. First, a Steiner tree is built interconnecting the clients. This treeis constructed even in the presence of obstacles and, by definition,is the smallest Euclidean tree interconnecting the set of clients. Ina second phase, each robot runs a state machine, allowing the ad-hocnetwork to be created autonomously. The approach is decentralized,autonomous and able to deal with signal propagation phenomena. Wevalidate our approach though physical and simulated experiments andtheoretical analysis. The theoretical analysis provides a bound on themaximum number of networked robots to create the solution. The realexperiments, using the throughput metric, validate the approach inphysical environments.